PENGEMBANGAN FLIPBOOK INTERAKTIF BERBASIS PJBL UNTUK MENINGKATKAN KETERAMPILAN MENGGAMBAR TEKNIK - Mojibur Rohman; Priska Choirina; Tri Ayu Tirta Kumala (Steam Engineering, 2026)
Engineering Drawing is one of the compulsory courses and plays an essential role in Mechanical Engineering education. However, the learning process of engineering drawing often faces several challenges, such as low student engagement, difficulties in understanding projection and perspective drawings, and limited learning media. To address these issues, this study aims to develop an Interactive Flipbook-based teaching material integrated with Project-Based Learning (PjBL) as an innovative strategy for teaching Engineering Drawing. The interactive learning media was developed using Flipbook Maker software, which allows digital presentation of materials in a more engaging format, including dynamic illustrations, 3D animations, video tutorials, and interactive quizzes. Through the integration of the PjBL approach, students are assigned industry-based projects, such as creating detailed working drawings of machine components in a step-by-step manner. This research employs the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Evaluation was carried out through trials involving students, assessing improvements in drawing skills, understanding of drawing standards, and the overall effectiveness of project-based learning. The results show that the interactive Flipbook based on PjBL received a very valid rating from material experts (87) and a valid rating from media experts (84.2). Moreover, student trials demonstrated significant improvements in conceptual understanding, engineering drawing skills, and learning motivation.